Special issue in memory of professor Alistair Anderson 'Social Perspectives of Entrepreneuring'. Issue 7 (8th August 2022) - Jack, Sarah; Gaddefors, Johan
ABSTRACT: This Special Issue of Entrepreneurship and Regional Development honours Distinguished Professor of Entrepreneurship Alistair Anderson's memory. This Special Issue offers a range of papers that engage with Alistair Anderson's work and extend it by taking a social science view to understanding entrepreneurship.